Neuroimmunogastroenterology: At the Interface of Neuroimmunology and Gastroenterology - Sanchez, John Michael S.; McNally, J. Scott; Cortez, Melissa M.; Hemp, James; Pace, Laura A.; Clardy, Stacey L. (Frontiers in Neurology, 2020)
The central nervous system (CNS) is an important regulator of the gastrointestinal tract, and CNS dysfunction can result in significant and disabling gastrointestinal symptom manifestation. For patients with neuroimmunologic and neuroinflammatory conditions, the recognition of gastrointestinal symptoms is under-appreciated, yet the gastrointestinal manifestations have a dramatic impact on quality of life. The current treatment strategies, often employed independently by the neurologist and gastroenterologist, raise the question of whether such patients are being treated optimally when siloed in one specialty. Neuroimmunogastroenterology lies at the borderlands of medical specialties, and there are few resources to guide neurologists in this area. Here, we provide an overview highlighting the potential mechanisms of crosstalk between immune-mediated neurological disorders and gastrointestinal dysfunction.